Urban Geese – looking to North America for experiences to guide management in Europe? - Fox, Anthony D. (Wildfowl, 2019)
Free-flying geese have become a problem in many parts of urban North America as a result of accidental escapes, deliberate (re-)introductions and colonisation by naturally expanding populations. In the last 25 years, the same problem is becoming manifest in Europe. Such urban goose populations tend to benefit from access to highly suitable managed, fertilised short-cut grasslands (available at, for instance, golf clubs, sports fields, industrial estates) and other productive feeding sites close to safe open-water night-time roost sites. This behaviour brings elevated reproductive success (due to reduced predation risk) and survival rates (due to reduced hunting and predation rates) compared to other goose populations. As a result, numbers have tended to increase as urban geese habituate to their proximity with humans. Fouling and contamination, disease and parasite transmission, impacts on biodiversity, public safety issues and simple nuisance factors represent some of the conflicts most frequently perceived and/or posed by increasing number of geese in urban environments. Literature reviews show that there are nutritional, energetic, foraging, thermal and fitness (both reproductive and survival) benefits for geese from using urban habitats compared to rural ones, underlining the potential for an increasing problem in the future. Solving urban wildlife issues is particularly challenging because sectors of the public may hold different views on the magnitude of the problem, and the urgency for and the nature of resolution. For this reason, management solutions to urban goose issues require sensitive and effective engagement with all stakeholders involved to ensure ownership of the process, to find solutions to opposing views and to gain agreement on the scale and nature of potential solutions prior to tackling problems. Potential local management mechanisms include removal of the food supply (e.g. by stopping provision of food, keeping potential feeding habitats in an unsuitable state, using chemical repellents, etc.), scaring and relocation/removal of geese from conflict loci, but all these actions have their limitations and costs. Population control includes rendering nests unproductive or chemical contraception, but in long-lived birds such as geese, elevating adult mortality is far more effective at reducing population size than reducing reproductive output. We need to improve our understanding of the population dynamics of urban goose populations, be better able to communicate biological information to those charged with their management, have a better understanding of the values and perceptions of urban geese held by the wider public, and improve our ability to resolve conflicts between sectors of society with differing views on urban goose management, if we are to be better prepared for resolving such conflict in the future.